The SAGE handbook of social work. - Gray, Mel, 1951-; Midgley, James, 1944-; Webb, Stephen A., 1956- (London : Sage Publications, 2012)
This Handbook is the world's first generic major reference work to provide an authoritative guide to the theory, method, and values of social work in one volume. Drawn from an international field of excellence, the contributors each offer a critical analysis of their individual area of expertise. The result is this invaluable resource collection that not only reflects upon the condition of social work today but also looks to future developments. Split into seven parts, the Handbook investigates: Policy dimensions ; Practice ; Perspectives ; Values and ethics ; The context of social work ; Research ; Future challenges. It is essential reading for all students, practitioners, researchers, and academics engaged in social work.
The SAGE Handbook of Social Work is the world's first generic major reference work to provide an authoritative guide to the theory, method, and values of social work in one volume. Drawn from an international field of excellence, the contributors each offer a critical analysis of their individual area of expertise. The result is this invaluable resource collection that not only reflects upon the condition of social work today but also looks to future developments. Split into seven parts, the Handbook investigates: > Policy dimensions > Practice > Perspectives > Values and ethics > The context of social work > Research > Future challenges It is essential reading for all students, practitioners, researchers, and academics engaged in social work.
Keywords: Maatschappelijk werk; Public welfare; Social policy; Social service